1976
DOI: 10.1001/jama.236.19.2209
|View full text |Cite
|
Sign up to set email alerts
|

Sauna-takers disease. Hypersensitivity pneumonitis due to contaminated water in a home sauna

Abstract: Daily saunas taken by a young man were followed by fever, chills, malaise, dyspnea, cough, and myalgia from six to eight hours later. Symptoms, which were related to pouring water from a sauna bucket over the heating element, progressed to chronic dyspnea and fatigue. Serial serum samples showed precipitin reactions to bucket water and extracts of bucket mold. IgG antibody activity, demonstrated by radioimmunoassay, suggested that Pullularia was a major antigen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
3

Year Published

1984
1984
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 9 publications
1
19
0
3
Order By: Relevance
“…A few studies from Sweden and Finland have reported allergic reactions directly caused by mold-contaminated water (9,41,43 in the growing epidemic of allergy and asthma observed in the human population (27,30,32,33,38). The evidence linking molds like the Aspergillus, Cladosporium, and Penicillium species with severe asthma was recently reviewed and found to be strong (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies from Sweden and Finland have reported allergic reactions directly caused by mold-contaminated water (9,41,43 in the growing epidemic of allergy and asthma observed in the human population (27,30,32,33,38). The evidence linking molds like the Aspergillus, Cladosporium, and Penicillium species with severe asthma was recently reviewed and found to be strong (14).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have revealed species that may produce unwanted flavors and odors in water (10,46) and species of technical concern that have the ability to oxidize pipe surfaces in the water distribution network (19). Reports from Sweden and Finland have indicated allergic and respiratory health effects of fungi resident in water (9,41,43).…”
mentioning
confidence: 99%
“…Dry saunas are maintained at elevated temperature, and due to the traffic of users, they are exposed to various microorganisms, which may be periodically removed by cleaning and disinfection (9).…”
Section: Introductionmentioning
confidence: 99%
“…This is due, in part, to the fact that causal relationships between fungal occurrence and water quality remain uncertain. Nonetheless, waterborne fungi are likely associated with taste and odor problems, contamination in food and beverage preparation, and a variety of health-related effects (3,5,10,17). Uncertain ramifications of fungi in potable water have led to a limited number of investigations which show that fungi are present in a significant proportion of tap water samples; however, species abundance and diversity are extremely variable (6,11,13,16).…”
mentioning
confidence: 99%